Aggressive form of Pancreatitis Worsened by Tuberculous Pleuritis - Manea, Rosana; Raicu, Lavinia (Archives of Clinical and Medical Case Reports, 2020)
Pancreatitis is an acute or chronic inflammatory condition caused by the disruption of exocrine pancreatic cells by the invasion of inflammatory cells. There are two subtypes of pancreatitis: interstitial edematous pancreatitis and necrotising pancreatitis. One of the most common cause of acute and chronic pancreatitis is alcohol use. Diagnostic criteria are usually used where a patient has distinctive signs, elevated amylase and lipase levels, and specific imaging findings. Treatment is usually supportive, there is no particular pharmacotherapy for this disorder [1]. We present the case of a 37-year-old man known with chronic pancreatitis worsened by massive pleural effusion with TB, presented to our hospital with shortness of breath. Globally, the incidence of TB effusions is higher in younger patients. Confirmed diagnosis was based upon histopathological and CT imaging results.